2019
DOI: 10.1021/acs.chemmater.8b04756
|View full text |Cite
|
Sign up to set email alerts
|

Facile One-Pot Synthesis of Pd@Pt1L Octahedra with Enhanced Activity and Durability toward Oxygen Reduction

Abstract: A successful strategy for reducing the content of Pt without compromising the activity of a Pt-based catalyst is to deposit Pt as an ultrathin overlayer on the surface of another metal. Here, we report a facile one-pot synthesis of Pd@Pt1L (1L: one atomic layer) core–shell octahedra using a solution-phase method. The success of this method relies on the use of metal precursors with markedly different reduction kinetics. In a typical synthesis, the ratio between the initial reduction rates of the Pd­(II) and Pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…It should be pointed out that although the presence of Pd cores would block the inner surface of a Pt shell, it allows one to reduce the thickness of the Pt shell down to one atomic layer, which would substantially increase the utilization efficiency of Pt atoms . Additionally, as reported in our recent work, the presence of Pd in the core could greatly improve the thermal stability of Pd@Pt core‐shell icosahedra relative to the Pt icosahedral nanocages .…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…It should be pointed out that although the presence of Pd cores would block the inner surface of a Pt shell, it allows one to reduce the thickness of the Pt shell down to one atomic layer, which would substantially increase the utilization efficiency of Pt atoms . Additionally, as reported in our recent work, the presence of Pd in the core could greatly improve the thermal stability of Pd@Pt core‐shell icosahedra relative to the Pt icosahedral nanocages .…”
Section: Resultsmentioning
confidence: 63%
“…[33] With the use of ap roper combination of reducing agent and reaction temperature, the initial reduction rate for the Pd II precursor could also be tuned to the right range for the generation of Pd nanocrystals with an icosahedral structure. [34] Figure 1a shows as chematic illustration of the one-pot approach, which involves the use of tetraethylene glycol (TTEG)a sasolvent and ap recursor to the reducing agent,a scorbic acid (AA) as a co-reducing agent, and poly(vinyl pyrrolidone) (PVP) as ac olloidal stabilizer.B ased on the resultso farecent study, [35] we identified Na 2 PdCl 4 andP t(acac) 2 as an appropriate combination of precursors to Pd and Pt, respectively,f or the proposed one-pot synthesis. When optimized, the overall synthesis can be programmed to occur in two well-separated steps (Figure 1a).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…These advanced electrocatalysts are classified as platinum group metal (PGM), non-PGM catalysts, carbon-based catalysts, and single-atom-based catalysts. An example for PGM catalysts is Pt–Pd alloy or a core–shell structure [ 9 ], which show enhanced activity and durability for ORR. Platinum (Pt) and its alloys are considered as the best electocatalysts for ORR, which carries out the reaction through the 4-electron pathway with the formation of only water as the product [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%